Simuliranje nastajanja gruč dispergiranih delcev pod vplivom zunanjega magnetnega polja - Pristovnik, Andrej (Strojniški vestnik, 2002)
Magnetic water-treatment (MWT) devices for scale control can be used with good economic and ecological benefits. From experimental results under well-controlled laboratory conditions we have established that the effects of MWT devices are very dependent on the composition of the treated dispersion system and their working conditions. To investigate the effects of magnetic field on the process of cluster formation in a fine-particle dispersion under the influence of the external magnetic field of a MWT device a theoretical model based on the Derjagin-Landau and Verway-Overbeek (DVLO) theory and the statistical Monte Carlo Metropolis method was used. The open-source computer programs for the simulation and the graphical presentation of clustering under the influence of an external magnetic field were developed. The results were analysed by cluster analysis, based on the partitioning and hierarhical methods.
Keywords: obdelava vode magnetna; vodni kamen; metode Monte Carlo Metropolis; analize gruč; disperzni sistemi; magnetna obdelava vode; DLVO teorija; metoda Monte Carlo; Monte Carlo method